Dissolved organic matter (dom) and heavy metals in waterfalls water in Kelantan - Abdul Mutalib, Abdullah (PPSP, Universiti Sains Malaysia, 2007)
The water samples were collected from Linag and Pasu waterfalls, and Top Bok hot spring, situated in Kelantan, Malaysia The sampling and sample treatment was made according to EPA protocols. Physicochemical measurements of water samples were performed on site using YSI® 556 Multi-Probe System. DOM fractions were made with membrane filtration, and total DOM was trapped on C-18 and XAD-4 columns through the SPE technique. The metallic elements were determined in water samples using F AAS and GF AAS. Amberlite XAD-4 Resin was found to have more capacity to enrich total DOM than the C-18 column and membrane filter. The FT-IR spectra of the retentate showed bands for -OH, -CH, C=O and C-0-C stretching vibrations for phenolic, carboxylic and carbohydrate functional groups. The metals determined were Pb (II), Fe (II), Cu (II), Cd (II) and Zn (II); their concentration varied between samples, and overall concentrations were within the safe limits set by EPA and WHO for water used in bathing and tourism activities.